Patient-Specific Quantitation of Mitral Valve Strain by Computer Analysis of Three-Dimensional Echocardiography: A Pilot Study. (January 2016) - Ben Zekry, Sagit; Freeman, Jeff; Jajoo, Aarti; He, Jiwen; Little, Stephen H.; Lawrie, Gerald M.; Azencott, Robert; Zoghbi, William A.
Abstract : Background—: A paucity of data exists on mitral valve (MV) deformation during the cardiac cycle in man. Real-time 3-dimensional (3D) echocardiography now allows dynamic volumetric imaging of the MV, thus enabling computerized modeling of MV function directly in health and disease. Methods and Results—: MV imaging using 3D transesophageal echocardiography was performed in 10 normal subjects and 10 patients with moderate-to-severe or severe organic mitral regurgitation. Using proprietary 3D software, patient-specific models of the mitral annulus and leaflets were computed at mid- and end-systole. Strain analysis of leaflet deformation was derived from these models. In normals, mean strain intensity averaged 0.11±0.02 and was higher in the posterior leaflet than in the anterior leaflet (0.13±0.03 versus 0.10±0.02; P <0.05). Mean strain intensity was higher in patients with mitral regurgitation (0.15±0.03) than in normals (0.11±0.02; P =0.05). Higher mean strain intensity was noted for the posterior leaflet in both normal and organic valves. Regional valve analysis revealed that both anterior and posterior leaflets have the highest strain concentration in the commissural zone, and the boundary zone near the annulus and at the coaptation line, with reduced strain concentration in the central leaflet zone. Conclusions—: In normals, MV strain is higher in the posterior leaflet, with the highest strain at the commissures, annulus, and coaptation zones. Patients with organic mitral regurgitation have higher strain than normals. Three-dimensional echocardiography allows noninvasive and patient-specific quantitation of strain intensities because of MV deformations and has the potential to improve noninvasive characterization and follow-up of MV disease. Abstract : Supplemental Digital Content is available in the text.